Uji Aktivitas Enzim Xilanase Ekstraselular dan Intraselular Bakteri Endofitik Tanaman Brucea javanica (L.) Merr. - Shirly Kumala; Wibowo Mangunwardoyo; Diah Dethriani (Fakultas Farmasi Universitas Pancasila, 2006)
Assay for xylanase enzyme activity of endophytic bacteria from Brucea javanica (L.) Merr. has been carried out. Parts of the plants used in this study were stem, leave and fruit. Samples were collected from Bogor, Cianjur and Tawangmangu. To evaluate the enzyme activity the fungi were shakefermented for 14 days. The supernatant were used to examine the extracellular enzyme and biomass for intracellular enzyme, using DNS methode to test the activity of enzyme. The results showed that from ten isolates only four isolates produced xylanase enzyme. Isolate 2.3.1 and 2.3.6 produced extra and intracellular enzyme, while isolate 2.1.15 and 2.3.13 only produced extracellular xylanase enzyme.